'Die Klippe Swyg!' Artefakte, ekofakte, tekste, godsdiens en geskiedenis : argeologie en die Bybelwetenskappe as gespreksgenote - Boshoff, Willem (Old Testament essays, 2007)
A problem for those interested in the relationship between archaeology and the Bible is that it is a problematical relationship. It is not easy to define how the two are actually related, because underlying both the Bible and any site of archaeological interest, are complex histories. After a brief overview of the subject Biblical Archaeology at the University of South Africa, a more extensive overview of the history of Biblical Archaeology is presented. It is based on the periodisation of Roger Moorey in his book A century of Biblical Archeology (1991). The scene is currently characterised by ongoing excavations, too few final reports, the publication of encyclopaedic overviews and histories of Israelite religion. The question is: if Biblical Archaeology is viewed as Historical Archaeology, do artefacts and ecofacts stand in opposition to texts and historiography? Texts can play two parts in Historical Archaeology : They can be found in the archaeological process, as artefacts, and they can be used as sources to shed light on historical situations reflected in the material remains, where literate observers were present to describe the situation. Biblical texts have been found and used in both these historical archaeological situations, e.g. as artefacts at Qumran and as sources at the excavations and interpretation of finds relating to Lachish. Examples of historical archaeological character from the Phoenician harbour town Dor and the South African situation are employed to illustrate some of the problematic issues in a more neutral environment.